DENTISTS' KNOWLEDGE, ATTITUDE AND PERCEPTION OF FAMILY EDUCATION TOWARDS THE TRAUMATIC DENTAL INJURIES IN PEDIATRIC POPULATION IN IASI - Cioata Radu; Alice Murariu; Adriana Balan; Laura Gavrila; Carmen Savin (Romanian Society of Oral Rehabilitation, 2017)
Aim: is to evaluate dentists' knowledge and attitude in relation to the management of the emergency treatment in the traumatic dental injury in children and teenagers as well as the level of parents' information. Material and methods: We elaborated our own 23 question questionnaire that was distributed to a number of 151 dentists of Iasi, both general dentists and pediatric dentists. Results: The study results show that the generalists have less knowledge about the traumatic dental injury as compared to the pediatric dentists, and the level of information of the families is also reduced. We also identified other factors that may have negative effects on the successful treatment of these disorders such as the low professional expertise of the dentists, their attitude by avoiding such patients, the fear of failures and complications, the lack of cooperation from the part of parents or the cover of some additional costs. Conclusion: We consider as necessary the organization of continuous medical education courses on these topics and the introduction of oral health educational programmes in the school curriculum that might provide useful information both for parents and teachers.